Storage system and power consumption reduction method for the same - NAKANO TAKAHIRO; MATSUZAWA KEIICHI (2013)
In a storage system that includes two or more file servers each including an arbitrary number of operating virtual file servers, a management server: holds a load information table regarding a load on each virtual file server for each time period and redundancy information table for the storage system; judges, with reference to the load information table and redundancy information table, whether or not the loads on the virtual file servers can be handled by a smaller number of file servers than the number of currently-operating file servers; selects, if the judgment result is positive, a power-off target file server and makes another file server fail over a virtual file server in the power-off target file server; and turns off the power-off target file server.